EFFORTS OF THE WOMEN AND CHILDREN PROTECTION UNIT (PPA) IN RECOVERING PSYCHOLOGICAL AND DEEP TRAUMA IMPACTS ON VICTIMS OF SEXUAL VIOLENCE AT THE LOMBOK TIMUR POLICE STATION - Putra, I Made Dharma Yulia (Universitas Airlangga, 2024)
The Women and Children Protection Unit is one of the institutions responsible for upholding the law. The PPA Unit is required to participate in supporting the realization of protection and overcoming criminal acts of violence against children, therefore the government has passed Law Number 35 of 2014 concerning Child Protection and Law Number 23 of 2004 concerning the Elimination of Domestic Violence, so that the Women and Children Protection Unit of the East Lombok Resort Police is required to be able to assist in the process of resolving and dealing with criminal acts of violence against women and children. The aim of this research is to analyze and understand the optimization of the services of the Women and Children Protection Unit (PPA) in recovering from the psychological impacts and deep trauma of victims of sexual violence at the East Lombok Police and to analyze and understand the obstacles to the Women and Children Protection Unit (PPA) of the East Lombok Police in Providing Recovery Services for the Psychological Impact and Deep Trauma of Sexual Violence Victims. The research method used in this research is Empirical Law. The results of this research are that the number of women who experience sexual violence is still very high. The state in its constitution is responsible for the protection, promotion, enforcement and fulfillment of the human rights of every individual as explained in Article 28I of the 1945 Constitution of the Republic of Indonesia. The state's protection for victims of sexual violence can also be seen from the formation and ratification of the Law. Number 12 of 2022 concerning Crime of Sexual Violence. In handling cases of sexual violence, a Women and Children Protection Unit was formed, this unit is specialized in handling victims, witnesses or suspects involving women and children who require special handling. The efforts that have been made by this unit to deal with cases of violence experienced by women and children are non-penal and penal efforts. The PPA Unit's optimization of victim recovery can also be seen in the case handling process as well as collaboration with community institutions and psychologists. Obstacles to victims' recovery are quite frequent and pervasive in society